PENGARUH FASILITAS KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KABUPATEN MALUKU TENGAH - Orgenes Pelasula; Chyntia Imelda Tjokro; Deflin Tresye Nanulaitta; Carla Carolien Tousalwa (P3M Politeknik Negeri Ambon, 2024)
This research aims to analyze the influence of work facilities on employee performance at the General Section of the Central Maluku district office. The research method used was simple linear regression analysis with a sample of Central Maluku District General Office employees. This research uses a quantitative approach with data collected through questionnaires distributed to Central Maluku District General Office employees. Data analysis uses simple linear regression to test the influence of the independent variable (work facilities) on the dependent variable (employee performance). The research results show that work facilities have a positive and significant effect on employee performance with a regression coefficient of 0.513. The practical implications of the research are the need to improve facilities and develop employee capabilities to increase efficiency, effectiveness and quality of public services. Keywords: Work Facilities, Employee Performance